Development pattern of tracheal cartilage in human embryos. Issue 5 (8th October 2020) - Fockens, M. Matthijs; de Bakker, Bernadette S.; Oostra, Roelof‐Jan; Dikkers, Frederik G.
Abstract: Introduction: Congenital tracheal anomalies are associated with high morbidity and mortality. The etiology of congenital tracheal anomalies is not well understood, but often attributed to malformed tracheal cartilage. The development of tracheal cartilage has not been described in detail. In this study, we aimed to investigate the development pattern and timing of normal tracheal cartilage to better understand the etiology of tracheal anomalies. Materials and methods: The development of tracheal cartilage was examined by studying the trachea in histological sections of 14 healthy human embryos from the Carnegie collection. Two specimens for Carnegie Stages 17–23 (42–60 days of embryological development) were studied. Results: At Carnegie Stages 17–19 (42–51 days), a continuous mesenchymal condensation was observed ventral to the tracheal lumen. At Stages 20 and 21 (51–54 days), this pre‐tracheal mesenchyme showed sites of increased condensation indicative of future tracheal rings. Furthermore, growth centers were identified both proximally and distally in the trachea. Characteristic horseshoe shaped tracheal rings were apparent at Carnegie Stages 22 and 23 (54–60 days). Conclusions: In human embryos, tracheal rings arise from growth centers in the ventral mesenchyme at approximately 51–54 days of embryological development. The observation of proximal and distal growth centers suggests a centripetal growth gradient, potentially contributing to occurrence of complete tracheal ring deformity (CTRD). Although this study shows new insights on tracheal cartilage development, the exact origin of congenital tracheal defects has yet to be elucidated.